The Variation of Consumer Anthropomorphism across Cultures - Hart, Phillip M.; Jha, Subhash (Indian Journal of Marketing, 2015)
Over the last 8 years, marketing research has begun to empirically probe consumer anthropomorphism or instances when consumers treat a product as human in one or more ways. Though theories of anthropomorphism commonly recognize that the phenomenon varies across cultures, no empirical effort in marketing or any other discipline has demonstrated this. The present research conducted a survey in India and the United States regarding four products commonly owned by students. The results demonstrated that for Indian consumers, product anthropomorphism is more commonplace, but less influential on their product evaluations as compared to American consumers.